Macronutrient deficiencies in soybean cv. BRSMG 68 (Vencedora) cultivated in nutritive solution - Prado, Renato de Mello; Franco, Claudenir Facincani; Puga, Aline Peregrina (Comunicata Scientiae, 2010)
Soybean is a crop of great importance for Brazil, and knowledge of their nutritional status allowsproduction and high quality products. Thus, the present work aimed to evaluate the culture of thesoybean cv. BRSMG 68 (Vencedora), submitted to macronutrients omission on the development,nutritional status and the visual symptomatology of nutrient deficiency. The design used wascompletely randomized, with seven treatments that corresponded to the complete (macro andmicronutrients) solution and the individual omission of N, P, K, Ca, Mg and S. The treatments wereapplied two weeks after the emergency of the soybean. The nutrient solution was constantlyoxygenated and replaced weekly, and the pH monitored daily remained around 5. After six weeksof application of the treatments, the height of the plants, number of leaves, stem diameter wasevaluated, matter dry accumulated in the roots, it leaves aerial and the nutritional state and thecharacterization of the visual symptoms. The macronutrient deficiency promoted a decreasein production of root and shoot dry mass of soybean cultivar BRSMG 68 (Vencedora) in nutrientsolution, for the full treatment. The most limiting nutrient for dry matter production of soybeancompared to complete treatment were N, S and K, with decreases of 90, 76 and 73%, respectively.Individual omissions resulted in morphological changes, which were translated by characteristicvisual symptoms of nutritional deficiency of the respective nutrient.